Obesity modulates diaphragm curvature in subjects with and without COPD - Boriek, Aladin M.; Lopez, Michael A.; Velasco, Cristina; Bakir, Azam A.; Frolov, Anna; Wynd, Shari; Babb, Tony G.; Hanania, Nicola A.; Hoffman, Eric A.; Sharafkhaneh, Amir (American journal of physiology. Regulatory, integrative and comparative physiology, 2017)
Obesity is a common comorbidity of chronic obstructive pulmonary disease (COPD) and has been associated with worse outcomes. However, it is unknown whether the interaction between obesity and COPD modulates diaphragm shape and consequently its function. The body mass index (BMI) has been used as a correlate of obesity. We tested the hypothesis that the shape of the diaphragm muscle and size of the ring of its insertion in non-COPD and COPD subjects are modulated by BMI. We recruited 48 COPD patients with postbronchiodilator forced expiratory volume in 1 s (FEV1)-to-forced vital capacity (FVC) < 0.7 and 29 age-matched smoker/exsmoker control (non-COPD) subjects, who underwent chest computed tomography (CT) at lung volumes ranging from functional residual capacity (FRC) to total lung capacity (TLC). We then computed maximum principal diaphragm curvature in the midcostal region of the left hemidiaphragm at the end of inspiration during quiet breathing (EI) and at TLC. The radius of maximum curvature of diaphragm muscle increased with BMI in both COPD and non-COPD subjects. The size of diaphragm ring of insertion on the chest wall also increased significantly with increasing BMI. Surprisingly, COPD severity did not appear to cause significant alteration in diaphragm shape except in normal-weight subjects at TLC. Our data uncovered important factors such as BMI, the size of the diaphragm ring of insertion, and disease severity that modulate the structure of the ventilatory pump in non-COPD and COPD subjects.